Access to Surgical Treatment for Breast Cancer in the Philippines - Co`, Luis Miguel B (Archīum Ateneo, 2022)
Female breast cancer is the most commonly diagnosed cancer worldwide; however, while high-income countries have the highest incidence rates, lower-middle income countries have the highest mortality rates. In this article, we describe the landscape of disparities in access to surgical care for patients with breast cancer in the Philippines, a lower-middle income country in Southeast Asia. We describe the payment landscape that allows access to care for patients with non-metastatic disease, and draw attention to the fact that despite some degree of insurance for most Filipinos, great barriers to access remain in the form of a low number of surgical providers, geographic disparities, and persistent socioeconomic barriers. Lastly, we suggest steps forward to improve equity in access to surgical care for Filipino patients with breast cancer.